2011
DOI: 10.1016/s2255-4971(15)30198-1
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Abnormalities of the Talus in Patients With Clubfoot After Surgical Release Using the McKay Technique

Abstract: Objective: To analyze morphological abnormalities of the talus in patients with clubfoot after surgical treatment using the McKay technique. Method: Lateral standing-position radiographs of the feet of 14 patients with unilateral clubfoot who underwent treatment by means of the doubleincision McKay technique were retrospectively analyzed. All the patients were operated by the same surgeon, with an average of 6.53 years between surgery and the radiograph. We compared the radiographic characteristics of the talu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…Eight parameters characterizing the shape of the tarsal bones were measured/calculated as previously described (Fig. 2a-e) [13,14,20]: Talar length (TL), the radius of the trochlea tali (RT) and the talar height (TH) were measured in the lateral view of the foot and the ratio radius/length (RT/LT) was calculated accordingly. To describe the angular segment available for tibiotalar dorsiflexion the "anterior talar motion segment" (ATM) was measured in the lateral view.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight parameters characterizing the shape of the tarsal bones were measured/calculated as previously described (Fig. 2a-e) [13,14,20]: Talar length (TL), the radius of the trochlea tali (RT) and the talar height (TH) were measured in the lateral view of the foot and the ratio radius/length (RT/LT) was calculated accordingly. To describe the angular segment available for tibiotalar dorsiflexion the "anterior talar motion segment" (ATM) was measured in the lateral view.…”
Section: Methodsmentioning
confidence: 99%
“…Radiographic and sonographic studies on the development of tarsal bone shape in treated clubfeet revealed marked differences from normal feet but observed also some methodological difficulty in detecting morphological differences with these imaging modalities [ 6 10 ]. Additionally, it is unknown whether severe tarsal bone deformities, often observed after primary surgical therapy of clubfeet, occur or persist after the Ponseti treatment [ 11 14 ]. Clinical experience with residual clubfoot deformities in adult patients shows that in many cases the condition of the ankle will determine the long-term clinical outcome [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1. Talar sphericity patterns: (A) normal, enabling good mobility of the joint, (B) slightly flattened, (C) greatly altered or flat 7. …”
mentioning
confidence: 99%